PENGEMBANGAN USAHA SOUVENIR “THEBEMBEB” BAHAN BAKU RESIN DI KOTA PANGKALPINANG - Ichsan Ananda Putra; Reza Widhar Pahlevi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Nowdays, tourism is also a modern commodity which opens many new business opportunities. So that, it can become an support income for an area, especially the community with new jobs and business opportunities for the community. Tourism business opportunities that include culinary and souvenirs are two things that cannot be separated in supporting the tourism sector. If all elements of society synergize in terms of the development of the tourism sector, it is not impossible for the tourism sector to be the backbone of regional and national economic support. By increasing tourism sector, the presence of souvenirs "thebembeb” is expected to meet the needs of the market and establish cooperation with tourist attractions, outlets, and even-organizers (EO). Souvenirs “thebembeb” marketing uses two marketing strategies that are through offline and online. First, the CEO will go offline by working with MSME actors such as tourist attractions, vape stores, even planners and souvenir outlets to market souvenir products “thebembeb”. The second strategy is through online. “thebembeb” markets their products through market places such as shopee, tokopedia and the like also through personal social media “thebembeb”. The purpose of the souvenir development plan "thebembeb" is not only to sell products but also provides the benefits to the community with the availability of jobs and provide opportunities for business partners such as MSMEs so as to increase sales and build harmonious relationships. On the other hand, “thebembeb” is expected to contribute to the regional income supporting, especially the income of the community from the lower economy